A common fungicide impairs stream ecosystem functioning through effects on aquatic hyphomycetes and detritivorous caddisflies. (1st June 2020) - Cornejo, Aydeé; Pérez, Javier; Alonso, Alberto; López-Rojo, Naiara; Monroy, Silvia; Boyero, Luz
Abstract: Fungicides can reach streams through runoff or adhered to leaf litter, and have the potential to adversely affect processes such as litter decomposition and associated communities. This study investigated the effects of chlorothalonil, a widely used fungicide, on litter decomposition, detritivorous invertebrates (larvae of the insect Sericostoma pyrenaicum ) and aquatic hyphomycetes (AHs), using stream microcosms. We considered the single and combined effects of two exposure modes: waterborne fungicide (at two concentrations: 0.125 μg L −1 and 1.25 μg L −1 ) and litter previously sprayed with the fungicide (i.e., pre-treated litter, using the application dose concentration of 1250 μg L −1 ). We also assessed whether fungicide effects on invertebrates, AHs and decomposition varied among litter types (i.e., different plant species), and whether plant diversity mitigated any of those effects. Invertebrate survival and AH sporulation rate and taxon richness were strongly reduced by most combinations of fungicide exposure modes; however, invertebrates were not affected by the low waterborne concentration, whereas AHs suffered the highest reduction at this concentration. Total decomposition was slowed down by both exposure modes, and microbial decomposition was reduced by litter pre-treatment, while the waterborne fungicide had different effects depending on plant species. In general, with the exception of microbial decomposition, responses varied little among litter types. Moreover, and contrary to our expectation, plant diversity did not modulate the fungicide effects. Our results highlight the severity of fungicide inputs to streams through effects on invertebrate and microbial communities and ecosystem functioning, even in streams with well-preserved, diverse riparian vegetation. Highlights: Chlorothalonil risk assessment on stream communities and ecological processes. Microcosm assay to test single and combined effects of two different exposure modes. Litter pretreatment and waterborne fungicide impaired decomposers and detritivores. Litter diversity failed to mitigate any of the observed harmful fungicide effects. Fungicide management should consider their effects on aquatic ecosystems.